Product complexity and economic development - Arnelyn Abdon; Marife Bacate; Jesus Felipe; Utsav Kumar (Levy Economics Institute of Bard College, 2010)
We rank 5,107 products and 124 countries according to the Hidalgo and Hausmann (2009) measures of complexity. We find that: (1) the most complex products are in machinery, chemicals, and metals, while the least complex products are raw materials and commodities, wood, textiles, and agricultural products; (2) the most complex economies in the world are Japan, Germany, and Sweden, and the least complex, Cambodia, Papua New Guinea, and Nigeria; (3) the major exporters of the more complex products are the high-income countries, while the major exporters of the less complex products are the low-income countries; and (4) export shares of the more complex products increase with income, while export shares of the less complex products decrease with income. Finally, we relate the measure of product complexity with the concept of Complex Products and Systems, and find a high degree of conformity between them.
Keywords: O10; O14; 330; capabilities; development; economic complexity; diversification; method of reflections; product complexity; ubiquity